(3ZQjH GdMOjKs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3jgah (B: (3Ci jSbW hai cJGH dg (B( (3Udi Gddg Ydjg hSde (B) (3djghO JjeGA Ef dge GdPeI hYdjge GdLRjI HdGYOGA , GdfgGQ eOi hGddjd SOi s
(3BNQgG (B:s
(3hLGA ai GdMOjK (B" (3Cf GdeSdejf hGdeTQcjf deG EJdbhG ai hbYI fgGhfO YTjJge QjM bSWdGfjI (B" (3hgj GdefShHI Edi GdbSWd , hgh GdZHGQ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs